The Application of Socioscientific Issues (SSI)-Based Learning to Develop Scientific Argumentation Skills in the Production of Bio-foam (Biodegradable Styrofoam) from Sugarcane Bagasse - Qomariah, Nurul (SEAQIS Journal of Science Education, 2025)
SSI-based learning focuses on the complex problems that develop throughout society. SSI holds significant implications for society, requiring students, as the future generation, to actively participate in dialogue, discussion, debate, and argumentation. The purpose of this study is to analyse the development process of scientific argumentation skills in the production of bio-foam using sugarcane bagasse (Saccharum officinarum Linn). We have adopted a pre-experimental methodology, utilising a one-shot case study design. Students' observation sheets and SSI-based worksheets serve as research instruments, assessing their scientific analytical skills. The research findings reveal that students' implementation of SSI-based learning in the production of bio-foam from sugarcane bagasse demonstrates high competency and adherence to the learning stages. The average score of 87.6 fell into a very good category. The proficiency in completing the SSI-focused worksheets achieved an average score of 89.3; it was also classified as very good. The implementation of an SSI-focused study has led to the attainment of level 4 analytical skills in scientific argumentation for sugarcane bagasse production. This study reveals that students are capable of presenting argumentation skills with a single, clear counterargument. Therefore, implementing SSI-based learning in the production of sugarcane bagasse can enhance the development of scientific argumentation skills.